The Factors Affecting to Performance Efficiency of General Administration Officer, King Mongkut’s University of Technology North Bangkok - Jinda, Charindhorn (RMUTI Journal Humanities and Social Sciences, 2024)
The objectives of this research were study to 1) level of factors affecting to performance of general administration officer, King Mongkut’s University of Technology North Bangkok (KMUTNB) and 2) to study the work factors that affect the work efficiency of general administrative officer, KMUTB. The sampling for this study were 164 peoples. The tool that used to collect data is a questionnaire. The data were analyzed by frequency, percentage, mean, standard deviation and Multiple regression analysis. Results were that: (1) opinions on factors in the work of general administrative officers, KMUTNB were at high level, (2) opinions on factors affecting to performance efficiency of general administrative officers, KMUTNB were at high level and (3) factors in working in terms of job description, job success, and work environment. and welfare and compensation it affects the efficiency of the work of general administrative officer, KMUTB at statistical satisfaction 0.05 level.